Influence of titanium and zirconia substrates on the synthesis of inflammatory mediators - Moura Neto, João; Cardoso, Lais Medeiros [UNESP]; Pansani, Taisa Nogueira [UNESP]; Raucci, Larissa M. S. C.; de Souza Costa, Carlos Alberto [UNESP]; Basso, Fernanda G. (American Vacuum Society, 2023)
The repair and homeostasis of peri-implant tissues depend on several factors such as the local presence of pathogenic bacteria and their products. Among other events, peri-implant tissue response is also related to the implant material used, which interferes with cells and extracellular matrix interactions, affecting the osseointegration process. In this study, the influence of zirconia (Zr) and titanium (Ti) substrates on the response of preosteoblasts (MC3T3) and murine macrophages (RAW 264.7) exposed to lipopolysaccharide (LPS, P. gingivalis) was evaluated. Zr and Ti disks were obtained and subjected to surface roughness standardization, which was analyzed by scanning electronic microscopy (SEM). The cells were subsequently cultured on Zr and Ti surfaces in AlphaMEM culture medium for 24 h, followed by LPS stimulus for 4 h. The production of reactive oxygen species (ROS) and gene expression of inflammatory markers were determined. SEM images showed that Ti disks exhibited higher surface roughness than that of Zr disks. Cells that seeded onto Ti and Zr had increased expression of inflammatory mediators and ROS production in the presence of LPS; however, such cell responses were more evident for Ti disks. These data indicate that contact of cells with Zr surfaces may lead to a lower inflammatory potential than Ti surfaces. Elucidation of the inflammatory response triggered by LPS for cells in contact with titanium and zirconia may contribute to the selection of materials for installation of osseointegrated implants.